Factors Affecting Academic Performance of BS Food Technology Students - Gamboa, Marielle D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study aims to evaluate the factors affecting the academic performance of Bachelor of Science in Food Technology (BSFT) students of Bulacan Agricultural State College. Purposive sampling was used in the study wherein all BSFT students were instructed to answer a survey disseminated through social media platforms. The instrument comprises questions to obtain program selection information during admission test and a 5-point Likert scale (5-definitely true to me; 4-true to me; 3-uncertain; 2-not true to me; 1-definitely not true to me) to rate the given factors. Six factors were evaluated in this study which includes the course, study habit, learning style, motivation, teacher, and social factors. Results showed that the majority of students are positive in their academic performance. Students appear to be confident in their study habits. The BSFT students agree that the professors have demonstrated professional, ethical, and moral attitudes toward them. Results also showed that BSFT students express more compassion in their studies than in their social life. It is recommended that activities to improve the engagement of students in the program should be created. This could be done through immersion in some of the actual work of food technology professionals e.g. research and community involvement. Realizing their contribution to society may improve their perception of the course and enhance their study habits toward better academic performance.